An Analysis of Performance Comparison of Circuit Breaker Protection Systems in Packing and Picking Operations at PT. Shippindo Teknologi Logistik - Sianipar, Tigor Pangihutan; Wibowo, Pristisal; Tharo, Zuraidah (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2025)
The protection system in circuit breakers plays a crucial role in maintaining operational stability and safety in the logistics industry, particularly in the packing and picking processes, which involve high-capacity electrical equipment. This study aims to analyze and compare the performance of circuit breaker protection systems in the packing and picking operations at PT. Shippindo Teknologi Logistik, focusing on efficiency, safety, and equipment maintenance. The research methodology includes direct testing of the circuit breakers used in operational processes in the field. The analysis evaluates the capability of circuit breakers to respond to various electrical load conditions during the operation of packing and picking machines. Performance parameters such as response time to electrical disturbances, resistance to overcurrent, and frequency of automatic tripping were measured to compare the different types of circuit breakers used. The results indicate significant differences in the protection performance among the types of circuit breakers, particularly in terms of response time and resistance to current surges. Circuit breakers equipped with the latest technology demonstrated superior performance in maintaining system stability and minimizing equipment downtime. More responsive protection systems were found to enhance operational efficiency while reducing the risk of equipment damage and operational disruptions. In conclusion, the selection of an appropriate circuit breaker protection system significantly impacts the sustainability of packing and picking operations in the logistics industry. This study recommends adopting advanced protection technology circuit breakers to optimize performance at PT. Shippindo Teknologi Logistik